2017
DOI: 10.1080/20473869.2017.1407862
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with employment of mothers caring for children with intellectual disabilities

Abstract: Objectives: This study investigated employment, financial, and health issues of Japanese mothers with schoolaged children with disabilities, and factors associated with participants' employment. Methods: A survey was conducted with 243 Japanese mothers with children aged 6 to 18 years old enrolled in a Special Education Needs School for intellectually disabled children. The mothers' employment, income, health, and time spent caregiving were compared with those of other Japanese mothers using population data. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…DeRigne and Porterfield, 2010), as groups of parents who experience a different type of caregiving in comparison to parents of typically developing children (Jang, 2008). For example, in a recent study in Japan, Ejiri and Matsuzawa (2019) (DeRigne, 2012) or have more difficulties in working as paid employees than those who are parents of typically developing children (Kogan et al, 2008). Similar results were reported by Dillon-Wallace et al (2016), who found that the employees with children with SND reported higher levels of strain and fewer gains regarding work-life balance in comparison to employees with typically developing children.…”
Section: Disability Severitysupporting
confidence: 57%
See 2 more Smart Citations
“…DeRigne and Porterfield, 2010), as groups of parents who experience a different type of caregiving in comparison to parents of typically developing children (Jang, 2008). For example, in a recent study in Japan, Ejiri and Matsuzawa (2019) (DeRigne, 2012) or have more difficulties in working as paid employees than those who are parents of typically developing children (Kogan et al, 2008). Similar results were reported by Dillon-Wallace et al (2016), who found that the employees with children with SND reported higher levels of strain and fewer gains regarding work-life balance in comparison to employees with typically developing children.…”
Section: Disability Severitysupporting
confidence: 57%
“…Research has pointed to the needs of parents with children with SND (e.g., Brennan and Brannon, 2005;Steward, 2013) and with health care needs (e.g., DeRigne and Porterfield, 2010), as groups of parents who experience a different type of caregiving in comparison to parents of typically developing children (Jang, 2008). For example, in a recent study in Japan, Ejiri and Matsuzawa (2017) found that mothers of children with intellectual disabilities enrolled in special education schools had lower workforce participation and lower income, when compared to mothers with typically developing children. Other research studies have reported that mothers of children with severe disabilities invest less hours in their work, they are more likely to resign (DeRigne, 2012) or have more difficulties in working as paid employees than those who are parents of typically developing children (Kogan et al, 2008).…”
Section: Disability Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 243 mothers in Japan who were caring for children with intellectual disability showed that they had much a lower employment rate (49% compared with 71%) than mothers of unaffected children of the same age in the same region; 57% of these unemployed mothers wished to be in the workplace and 62% of mothers with an intellectually disabled child were in a lower income group. 26 Single-parent status, good health and college-level education, plus use of childcare and the child's age (>12 years old), were all positively correlated with paid work. 26 Similarly, a study from the USA found that the impact of having a child with ASD on the parent's workforce participation was influenced by whether the child also had an intellectual disability, and the parent's educational level, immigration status and ethnicity.…”
Section: Discussionmentioning
confidence: 93%
“…26 Single-parent status, good health and college-level education, plus use of childcare and the child's age (>12 years old), were all positively correlated with paid work. 26 Similarly, a study from the USA found that the impact of having a child with ASD on the parent's workforce participation was influenced by whether the child also had an intellectual disability, and the parent's educational level, immigration status and ethnicity. 25 An Australian qualitative study reported that, compared with other working Australians, mothers of children with intellectual disabilities had a higher educational level, yet poorer health, lower family income and lower workforce participation.…”
Section: Discussionmentioning
confidence: 93%